Tackling poverty at home and abroad: New Labour's public politics of poverty - Legge, Kate Eleanor (2012)
This thesis provides a timely retrospective of New Labour's public politics of global and domestic poverty through examination of their speeches and policy documents and secondary literature on the post-war politics of poverty and development, New Labour and public attitudes to poverty. It adopts a 'public politics' approach, in understanding these speeches and policy documents as public political discourse and understanding politics in broad cultural terms as the discursive struggle to embed a particular vision of the social world in the public imagination, and provides a rare example of a crossdomain study of New Labour, seeking to connect analysis of global and domestic policy. As such it contributes to what Colin Hay has called the 'new political science of British politics'. Both global and domestic poverty received a greater public political profile under New Labour than could have been envisaged in 1997. By the end of their first term they had made high-profile, time-specific commitments in both domains. Global poverty in particular gained unprecedented public attention in the build-up to the G8 Summit in 2005 and New Labour was centre stage in the political spectacle of Make Poverty History. This followed a period of neo-liberal dominance in which poverty was absent from the domestic political lexicon and subsumed by structural adjustment imperatives in the global domain. This comparative study of the public politics of poverty asks: whether New Labour made explicit connections between their global and domestic poverty discourses and commitments, and if so, what the nature of these connections were; what the 'narratives' employed to justify government action to tackle poverty were, and the similarities and differences between the two poverty domains; whether the general public shared these 'narratives' and, if not, how they differed; how New Labour's 'public politics of poverty' evolved over time in both global and domestic domains; and what the key characteristics of New Labour's public politics of poverty were, how could have differed, and what impact they appeared to have had on public opinion.